Peningkatan Hasil Belajar Bahasa Inggris Melalui Hypo Teaching Kelas X SMA 6 Padangsidempuan - Sibuea, Erni Rawati (Journal Education Innovation (JEI), 2025)
This research was conducted at 6 Padangsidempuan Private High School in class X for the 2024-2025 academic year. The population of this research was 120 students consisting of 3 classes, while the number of samples used in this research was 34 students. The research method used in this research is classroom action research which consists of three stages, namely practicum, cycle I and cycle II. In obtaining research results, the data collection tool in research for variable Meanwhile, the assessment for variable y is writing a drama script, plot, setting, actions (actions), characterization and point of view. From the results of the research carried out, the pre-action results obtained with an average score of 72.90, after learning was carried out in cycle I, there was an increase in the average score to 70.91 and in the second cycle treatment the average score of 90, 41 students was obtained. class X 6 Padangsidempuan Private High School 2024-2025 Academic Year 93.62. So in testing the hypothesis it can be concluded that there is a significant increase in student learning in writing drama scripts through the hynoteaching learning model, so it can be concluded that the hypothesis can be accepted